The Shephelah during the Iron Age recent archaeological studies - Lipshits, ʿOded 1963-; Maʾir, Aharon 1958- (Winona Lake, Indiana Eisenbrauns, 2017)
"The area of the Judean Foothills - the biblical Shephelah - has in recent years become one of the most intensively excavated regions in the world. Numerous projects, at sites of different types and utilizing various methodological approaches, are actively excavating in this region. Of particular importance are the discoveries dating to the Iron Age, a period when this region was a transition zone between various cultures--Philistine, Canaanite, Judahite, and Israelite. The current volume includes reports from eight of the excavations currently being conducted in the region (Azekah, Beth Shemesh, Gezer, Khirbet Qeiyafa, Tel Burna, Tel Halif, Tell es-Safi/Gath, and Tel Zayit), as well as a general study of the region by Ido Koch. The importance of this volume lies not only in the fact that it collects up-to-date reports on most of the current excavations in the region but also demonstrates the lively, at times even boisterous, scholarly discussions taking place on various issues relating to the archaeology and history of the Iron Age Shephelah and its immediate environs. This volume serves as an excellent introduction to current research on the Iron Age in this crucial zone and also serves as a reflection of current trends, methodologies, and approaches in the archaeology of the Southern Levant"--
Includes bibliographical references
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Excavations (archaeology) -- Israel -- Shephelah; Iron Age -- Antiquities -- Israel -- Shephelah; Shephelah (Israel) -- Antiquities; Aufsatzsammlung